Strategi Marketing Pop Mart dalam membentuk Perilaku Pembelian Impulsif - Arafani Dwi Susana; Marizka Nazla Yulita Putri; Erwin Permana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the past, toys were identified solely as instruments of entertainment for children. Adults were generally considered inappropriate to own or play with toys. Over time, toys have evolved into collectibles that have artistic, historical, and investment value for people of all ages. This study aims to analyze Pop Mart's marketing strategy in shaping impulsive buying behavior. The study was conducted using descriptive qualitative methods. The research data was obtained from digital searches and observations from various official sources and related official websites. The results of the study show that Pop Mart, as a leader in this industry, has successfully implemented marketing strategies that utilize collaborations with artists, the blind box concept, and the principle of scarcity to create a unique and attractive shopping experience for its consumers. Collaborations with artists play an important role in building brand identity and increasing product appeal. By offering limited editions of popular characters such as Molly, Labubu, and SkullPanda, Pop Mart has been able to attract collectors and art enthusiasts who have an emotional connection to these works. This has led to increased brand loyalty and purchase frequency. The blind box concept creates an element of surprise that triggers excitement when opening the packaging, thereby encouraging repeat purchases. Additionally, the scarcity marketing strategy, combined with the application of FOMO behavior, successfully creates a sense of urgency among consumers. Products with limited editions and purchase quantity restrictions create exclusivity, making consumers feel they must act quickly to obtain the product before it sells out.